(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Politeness can be realised in two important ways: Don’t impose and making him/her feel good are two ways to show Politeness (Lakoff, 1975). Negative face politeness and positive face politeness, as represented by these two methods, are critical components of Politeness when dealing with others’ faces. It would be considered polite for someone to show consideration and knowledge for the person they are speaking to if they are. There are major differences in the level of Politeness that can be observed in different communities. For example, if someone is more or less polite in a given community, this can be interpreted in different ways. Politeness in English and Arabic is examined in this study to see if there are any formulas for Politeness that can be translated between the two languages. For the Iraqi poet Mudafer AlNawab and Robert Forest, an American poet. linguistic Politeness is attempted Using one’s face to express Politeness in English is a way to free the speaker from the burden of imposition. Because people dislike being told what to do, getting what you want can be difficult. "Can you please pass me the newspaper?" rather than a command like "Give it to me," is preferable. Arab politeness is distinct from that of other Arabic-speaking cultures in that it is deeply intertwined with the Arab faith. Arabs are Muslims who have taken on the role of missionaries, going out into the world and bringing Islam to new lands. On the one hand, this is true; on the other hand, the language of the Quran and the Hadiths of the Prophets is Arabic. There are many Quranic and Prophetic Hadith references in the Arabic language because, according to Feghali (1997:347), the Arab population is between 85 and 90 per cent Muslim. Language in all Arabic communities is specialised as a polite community Adler, N. (1997), for example